FACTORS AFFECTING THE INTENTION TO USE O2O E-COMMERCE IN COMMUNITIES’ PRODUCTS PURCHASING OF GENERATION Y CUSTOMER - Saributr, Salitta; Hirankitti, Pimpa; Nilapornkul, Napaporn; Chaturongakul, Dolaya; Jathuwarodom, Akarawath; Poolmuangrat, Poonsak (RMUTT Global Business and Economics Review, 2021)
This research aimed 1) to study on the relationship between variables of perceived value, attitude, and intention to use O2O E-commerce; and, 2) to study on the transmission influence of the attitude in the relationship between perceived value and intention to use O2O E-commerce. Data collection was conducted using 349 online questionnaires to ask Generation Y customers with O2O E-commerce purchasing experiences according to the project of sustainable development of innovative products to communities of Rajamangala University of Technology Thanyaburi. Data analysis applied descriptive statistics to find out for the percentage, mean, and standard deviation. The inferential statistics were also used with a structural equation model for hypotheses testing. Direct influence was analyzed by regression method and the significance of indirect influence was analyzed by Bootstrapping. It was found that perceived value and attitude were the variables affecting the intention to use O2O E-commerce at the significant level of.05. Also, attitude was found to have the transmission influence on the relationship between perceived value and intention to use O2O E-commerce. According to the study results, it could be seen that customers perceived on the ease and benefits of products purchasing via O2O E-commerce. This indicated that there was no argument from the customers on the use of O2O E-commerce for products purchasing. Therefore, O2O E-commerce would be another choice for products distribution in this era, while sellers shall use diverse online and offline channels to provide content, plus adding more novel operations related to products for sale. Moreover, sellers must stress to form good attitude of customers toward O2O E-commerce by allowing them to perceive on the ease and benefits of use both online and offline channels in the same direction.